2017
DOI: 10.4049/immunohorizons.1700048
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 Is Upregulated in B-1a Cells by Chronic Self-Antigen Stimulation and Limits Generation of Natural IgM Plasma Cells

Abstract: B-1a cells are a unique population of innate-like B cells with a highly restricted and self-reactive BCR repertoire. Preimmune “natural” IgM produced by B-1a–derived plasma cells is essential for homeostatic clearance of cellular debris and forms a primary layer of protection against infection. In this study, we take advantage of a fluorescent reporter of BCR signaling to show that expression of the orphan nuclear hormone receptor Nur77 is upregulated under steady-state conditions in self-reactive B-1a cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…3B, 3C). A similar phenomenon has been described in both Ig HEL Tg and anti-Thy-1 (ATA) Tg mice lacking Thy-1 Ag (12,35). This stands in marked contrast to the B2 compartment in B1-8i mice, which is populated almost exclusively by VH186.2 H chain-expressing cells (Fig.…”
Section: Development Of B1a Cells Expressing the B1-8i H Chain Transgsupporting
confidence: 79%
See 1 more Smart Citation
“…3B, 3C). A similar phenomenon has been described in both Ig HEL Tg and anti-Thy-1 (ATA) Tg mice lacking Thy-1 Ag (12,35). This stands in marked contrast to the B2 compartment in B1-8i mice, which is populated almost exclusively by VH186.2 H chain-expressing cells (Fig.…”
Section: Development Of B1a Cells Expressing the B1-8i H Chain Transgsupporting
confidence: 79%
“…Selection into the innate-like B1a compartment requires the recognition of endogenous Ags sufficient to drive strong BCR signaling (12)(13)(14)(15). Consistent with the high self-reactivity of these cells, we recently showed that B1a cells express much higher levels of Nur77-eGFP reporter than B2 cells, and this was higher still among phosphatidylcholine-binding B1a cells that mark highly enriched, extremely self-reactive clones in this compartment (35). We first sought to determine whether NP + cells with low self-reactivity were indeed precluded from entering the B1a compartment in B1-8i mice.…”
Section: Development Of B1a Cells Expressing the B1-8i H Chain Transgmentioning
confidence: 53%
“…Next, to test in vivo relevance of these in vitro observations, we probed immune response to a T-independent BCR stimulus, NP-Ficoll. We previously reported enhanced IgM responses to NP-Ficoll immunization of Nr4a1-/-hosts and here observe profoundly increased IgG3 responses to this immunogen across multiple time points (Fig 6A) 30 . NP-Ficoll responses are completely dependent upon intact BCR signal transduction 47 .…”
Section: Nur77/nr4a1 Restrains Humoral Responses To Ag In the Absencesupporting
confidence: 77%
“…More recently, we have identified a role for NUR77/Nr4a1 in imposing a novel layer of B cell tolerance in vivo by mediating competitive elimination of chronically Ag-stimulated self-reactive B cells in settings with a limiting supply of the B cell survival factor BAFF 28 . We have similarly shown that NUR77 is upregulated by Ag in the highly self-reactive innate-like B1a population where it functions to restrain generation of natural IgM plasma cells 30 . Although expression of Nr4a genes is rapidly and robustly upregulated in response to acute BCR stimulation, their function in this context is unknown, and redundancy among the family members has never been explored in B cells.…”
Section: Introductionmentioning
confidence: 68%
“…133,134 Recently, we showed that Nur77-eGFP reporter expression was highly upregulated by chronic antigen stimulation in self-reactive B1a cells, particularly in highly self-reactive PtC-binding clones. 135 Unexpectedly, we found that deletion of Nr4a1 markedly increased the generation of B1a-derived natural IgM plasma cells, but did not expand the size of the B1a compartment. By contrast to ITIM-dependent inhibitory tone, Nur77 seems to regulate a distinct, downstream checkpoint by an unknown mechanism.…”
Section: Compe Titive Fitne Ss Of S Elf-re Ac Tive B Cell S In the mentioning
confidence: 61%